Hubungan Self Stigma dan Self Efficacy dengan Kepatuhan Minum Obat Anti Tuberkulosis pada Pasien TB Paru - Nadia Hamzah; Edwina R. Monayo; Sartika Sartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the association between self-stigma, self-efficacy, and adherence to Anti-Tuberculosis Drug (ATD) treatment among pulmonary tuberculosis patients. This study employed a quantitative research design with a cross-sectional approach. The results showed a significant association between self-stigma and adherence to ATD treatment (p-value < 0.05), as well as a significant association between self-efficacy and adherence to ATD treatment (p-value < 0.05). In conclusion, self-stigma and self-efficacy are psychological factors associated with adherence to ATD treatment among pulmonary tuberculosis patients. Lower levels of self-stigma and higher levels of self-efficacy are associated with better patient adherence throughout the course of treatment. Keywords: Medication Adherence, Pulmonary Tuberculosis, Self-Efficacy, Self-Stigma